(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: to perform a comparative assessment of oculomotor system mobility and visual system lability in patients with primary open-angle glaucoma (POAG) of stages II and III with compensated IOP. Material and Methods: A total of 38 patients (38 eyes) with POAG were examined. II stage was in 20 eyes and III stage was in 18 eyes. Oculomotor system mobility was studied according to impulse move frequency index, and visual system lability was assessed according to indices of critical flicker fusion and appearance frequency using an ophthalmic photomyostimulator unit (FMS-1). Results: Both in stage II and III of POAG, functional mobility of the oculomotor system was significantly lower as compared to the norm (р<0.05). Herewith, that was significantly lower in stage III than in stage II (р<0.05). Functional lability of the visual system in patients with stage POAG does not differ significantly from the norm. However, there is a significant reduction in visual system functional lability in stage III POAG as compared with the norm (р<0.01) and stage II of the disease (р<0.05). Conclusions: Obtained data indicate the need of searching the methods of stimulations of oculomotor system functional mobility and visual system lability in patients suffering from glaucoma, which can bring a vast improvement in the quality of life of these patients.